PROGRAM ECO-PESANTREN BERBASIS KEMITRAAN SEBAGAI UPAYA MEMASYARAKATKAN ISU-ISU LINGKUNGAN MELALUI PENDIDIKAN - Adam Diavano (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
Environmental problems have become a global problem, these problems arise due to increasing population and changing lifestyles to become more consumptive. The consequence of the above conditions is that the environment will be exploited causing natural disasters, various parties have tried to overcome environmental problems but the results have not been optimal. This is due to the low public awareness of the environment, therefore environmental education is needed from an early age. Eco-pesantren is a program based on the role of pesantren to preserve the environment through religious-based environmental education. Efforts to handle environmental problems such as the eco-pesantren program need to be addressed with a partnership pattern, because environmental problems are multi-stakeholder problems. The purpose of this study is to describe the partnership-based eco-pesantren program. The analysis carried out is a qualitative descriptive analysis using success indicators of eco-pesantren from Mangunjaya, while the research method uses literature studies. The partnership pattern that must be applied to support the eco-pesantren program is a partnership that includes partnerships in environmentally caring and cultured pesantren policies, partnerships in the development of environment-based curricula, partnerships in the development of participatory-based environmental activities, and partnerships in the management of environmentally friendly pesantren support facilities.